Synaptic reliability and temporal precision are achieved via high quantal content and effective replenishment: auditory brainstem versus hippocampus - Krächan, Elisa G (J Physiol, 2016)
KEY POINTS: Auditory brainstem neurons involved in sound source localization are equipped with several morphological and molecular features that enable them to compute interaural level and time differences. As sound source localization works continually, synaptic transmission between these neurons should be reliable and temporally precise, even during sustained periods of high‐frequency activity. Using patch‐clamp recordings in acute brain slices, we compared synaptic reliability and temporal precision in the seconds–minute range between auditory and two types of hippocampal synapses; the latter are less confronted with temporally precise high‐frequency transmission than the auditory ones. We found striking differences in synaptic properties (e.g. continually high quantal content) that allow auditory synapses to reliably release vesicles at much higher rate than their hippocampal counterparts. Thus, they are indefatigable and also in a position to transfer information with exquisite temporal precision and their performance appears to be supported by very efficient replenishment mechanisms. ABSTRACT: At early stations of the auditory pathway, information is encoded by precise signal timing and rate. Auditory synapses must maintain the relative timing of events with submillisecond precision even during sustained and high‐frequency stimulation. In non‐auditory brain regions, e.g. telencephalic ones, synapses are activated at considerably lower frequencies. Central to understanding the heterogeneity of synaptic systems is the elucidation of the physical, chemical and biological factors that determine synapse performance. In this study, we used slice recordings from three synapse types in the mouse auditory brainstem and hippocampus. Whereas the auditory brainstem nuclei experience high‐frequency activity in vivo, the hippocampal circuits are activated at much lower frequencies. We challenged the synapses with sustained high‐frequency stimulation (up to 200 Hz for 60 s) and found significant performance differences. Our results show that auditory brainstem synapses differ considerably from their hippocampal counterparts in several aspects, namely resistance to synaptic fatigue, low failure rate and exquisite temporal precision. Their high‐fidelity performance supports the functional demands and appears to be due to the large size of the readily releasable pool and a high release probability, which together result in a high quantal content. In conjunction with very efficient vesicle replenishment mechanisms, these properties provide extremely rapid and temporally precise signalling required for neuronal communication at early stations of the auditory system, even during sustained activation in the minute range.